Synergistic effect of nitrocellulose coating on structural and reactivity stabilization of ammonium nitrate oxidizer - Amir Abdelaziz; Djalal Trache; Ahmed Fouzi Tarchoun; Hani Boukeciat; Yash Pal; Sourbh Thakur; Weiqiang Pang; Thomas M. Klapötke (Defence Technology)
The present work aims to stabilize the room temperature allotropic transition of ammonium nitrate (AN) particles utilizing a microencapsulation technique, which involves solvent/non-solvent in which nitrocellulose (NC) has been employed as a coating agent. The SEM micrographs revealed distinct features of both pure AN and NC, contrasting with the irregular granular surface topography of the coated AN particles, demonstrating the adherence of NC on the AN surface. Structural analysis via infrared spectroscopy (IR) demonstrated a successful association of AN and NC, with slight shifts observed in IR bands indicating interfacial interactions. Powder X-ray Diffraction (PXRD) analysis further elucidated the structural changes induced by the coating process, revealing that the NC coating altered the crystallization pattern of its pure form. Thermal analysis demonstrates distinct profiles for pure and coated AN, for which the coated sample exhibits a temperature increase and an enthalpy decrease of the room temperature allotropic transition by 6 °C, and 36%, respectively. Furthermore, the presence of NC coating alters the intermolecular forces within the composite system, leading to a reduction in melting enthalpy of coated AN by ∼39% compared to pure AN. The thermal decomposition analysis shows a two-step thermolysis process for coated AN, with a significant increase in the released heat by about 78% accompanied by an increase in the activation barrier of NC and AN thermolysis, demonstrating a stabilized reactivity of the AN-NC particles. These findings highlight the synergistic effect of NC coating on AN particles, which contributed to a structural and reactive stabilization of both AN and NC, proving the potential application of NC-coated AN as a strategically advantageous oxidizer in composite solid propellant formulations.